The World Price of Foreign Exchange Risk - Dumas, Bernard; Solnik, Bruno (Journal of Finance, 1995)
We consider a world capital market in which the investor population is heterogenous. Investors of different countries differ in the prices of goods at which they consume the income from their investments. In such a setting, the international CAPM incorporates rewards for exchange rate risk, in addition to the traditional reward for market-covariance risk. The aim of the paper is to determine whether these additional risk premia empirically playa significant role in the pricing of securities. The test being conducted is a test of a conditional version of the CAPM. It builds on the recent empirical literature which points out that stock market returns may, to some extent, be predicted on the basis of a number of instrumental variables, such as interest rates and dividend yields. All previous tests of the international CAPM with exchange risk premia have been tests of the unconditional version and have been inconclusive.